A Qualitative Study on Formal and Informal Carers' Perceptions of Dementia Care Provision and Management in Malaysia - Goodson, Michaela; McLellan, Emma; Rosli, Roshaslina; Tan, Maw Pin; Kamaruzzaman, Shahrul; Robinson, Louise; Moloney, Susan (Frontiers in Public Health, 2021)
Background The number of people living with dementia (pwd) worldwide is increasing, particularly in low and middle income countries, where little is known about existing post-diagnostic care and support. This study aimed to understand healthcare provision for pwd in Malaysia, and to identify priorities for providing timely, quality, and accessible care and support to all. Methods Qualitative interviews with care providers and facilitators (health and community care professionals, paid carers, traditional medicine practitioners, faith healers, community leaders, non-governmental organisations). A piloted topic guide elicited understandings of dementia and dementia care, barriers and facilitators to care, and perceptions of key priorities for developing efficient, feasible and sustainable dementia care pathways. Verbatim transcription of audio-recorded interviews was followed by iterative, thematic data analysis. Results Twenty interviews were conducted (11 healthcare professionals, 4 traditional medicine practitioners, and 5 social support providers). Dementia care and support services exist in Malaysia, but these are not fully utilised. Despite locally recognised pathways of care, pwd still present with advanced disease. This was linked to a perception that symptoms of dementia are a normal sequelae of ageing. Earlier detection of dementia is opportunistic when patients present to clinicians with other ailments. A lack of specialists, overburdened clinics, and limited training and knowledge of dementia hinder early identification and management of dementia. Social care is largely the domain of families but some community-based support was available in some areas. Awareness raising for both the public and medical professionals, prevention, and more support from government are seen as key priorities to improve dementia management. Conclusions This qualitative study provides novel insight into the availability, delivery and use of post-diagnostic care and support in Malaysia from the perspective of care providers. Different care sectors are largely unaware of the services each other provides. Future work should explore how care provision across different service sectors and providers can be supported to better facilitate patient access and referral between primary, secondary and social care. The importance of supporting families was emphasised. Broad workforce training and development and improved awareness of dementia will enable use of preventive strategies and access to specialist services.